Coordinating with the "Inner GPS". Issue 6 (2nd April 2015) - Fenton, André A.
ABSTRACT: The 2014 Nobel Prize for Physiology or Medicine was awarded for the discoveries that have elucidated the components of the internal positioning system that is centered on the hippocampus and entorhinal cortex. Here I provide a less than objective discussion of the importance of these accomplishments to systems neuroscience. By identifying positioning components like place, direction, distance, borders and the like, the field is given the opportunity to have a shot at piecing together how these components are integrated into the synthetic positioning sense. We are also given what is in my view, the most experimentally accessible and therefore potentially understandable, cognitive representation. Lest we feel too confident in the completeness of our understanding, and to inspire redoubled curiosity, I briefly describe a preliminary observation from our work with the psychosis‐inducing drug phencyclidine (PCP). While PCP does not disturb where individual place cells fire, it dramatically discoordinates how these cells discharge together in time. Trying to understand how the positioning component cells are coordinated to provide useful knowledge is an exciting and tenable problem to be working on. © 2015 Wiley Periodicals, Inc.